2016
DOI: 10.1128/genomea.01192-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Six Chrysodeixis includens Nucleopolyhedrovirus Isolates from Brazil and Guatemala

Abstract: The baculovirus, Chrysodeixis (formerly Pseudoplusia) includens nucleopolyhedrovirus (ChinNPV), is a new Alphabaculovirus pathogenic to Chrysodeixis includens. Here, we report the complete genome sequences of six ChinNPV isolates. The availability of these genome sequences will provide information on ChinNPV molecular genetics, promoting understanding of its pathogenicity, diversity, and evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…This highly virulent virus could be a promising biological insecticide for control of C. includens [27], particularly given that resistance to chemical insecticides in this pest has become an issue of major concern in some regions [30,31,32,33]. As a result, attention has shifted toward alternative control measures against C. includens , including the characterization of different ChinNPV isolates [27,34], with the aim of obtaining novel and genetically diverse variants that may be employed as the basis for an effective biological insecticide.…”
Section: Introductionmentioning
confidence: 99%
“…This highly virulent virus could be a promising biological insecticide for control of C. includens [27], particularly given that resistance to chemical insecticides in this pest has become an issue of major concern in some regions [30,31,32,33]. As a result, attention has shifted toward alternative control measures against C. includens , including the characterization of different ChinNPV isolates [27,34], with the aim of obtaining novel and genetically diverse variants that may be employed as the basis for an effective biological insecticide.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that these isolates have the potential for controlling C. includens infestations in the field [13,14], and a biopesticide based on ChinNPV has been registered for control of C. includens in Brazil [15] that is effective on populations resistant to two chemical insecticides with different modes of action [16]. Analysis of the genetic sequences for ChinNPV isolates [17,18,19] indicated that they were members of a single alphabaculovirus species, Chrysodeixis includens nucleopolyhedrovirus , which was created and ratified by the ICTV in 2016 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Jehle et al proposed a phylogenetic species concept of baculoviruses based on nucleotide sequence distances of highly conserved genes [ 1 ]. Though family-wide phylogeny and the evolution of baculoviruses had been intensively studied, the intra-species diversity of baculoviruses was only recently addressed [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%